2022
DOI: 10.1055/s-0041-1737412
|View full text |Cite
|
Sign up to set email alerts
|

Dichlorination of β-Keto Esters and 1,3-Diketones Mediated by Oxone/Aluminum Trichloride Mixture in Aqueous Medium

Abstract: A new method for the α,α-dichlorination of β-keto esters using Oxone/aluminum trichloride mixture in aqueous medium has been developed. This useful process has also been applied successfully for the dichlorination of 1,3-diketones. The dichlorinated compounds have been produced in one step, high yields, and short reaction times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…In the event, we found that our product was completely identical with an authentical sample prepared by chlorination of tert-butyl acetoacetate (15) with AlCl 3 /oxone (Scheme 3). [12] It should be noted that using 2.5 equiv. of 1, a 38 % yield of 16 was achieved under the same reaction conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In the event, we found that our product was completely identical with an authentical sample prepared by chlorination of tert-butyl acetoacetate (15) with AlCl 3 /oxone (Scheme 3). [12] It should be noted that using 2.5 equiv. of 1, a 38 % yield of 16 was achieved under the same reaction conditions.…”
Section: Resultsmentioning
confidence: 99%